1999
DOI: 10.1074/jbc.274.25.17545
|View full text |Cite
|
Sign up to set email alerts
|

Role of Residues 311/312 in Actin-Tropomyosin Interaction

Abstract: The contraction of vertebrate striated muscle is regulated by the thin filament-associated proteins tropomyosin (Tm) 1 and troponin (Tn), which modulate the interaction of actin and myosin in a Ca 2ϩ -dependent fashion (2). Each Tm molecule associates with one Tn molecule and seven actin monomers. The amino acid sequence of Tm contains a pattern of charged and uncharged amino acids that repeats 14 times along its length (3). As each pair of repeats corresponds to an actin monomer along the actin filament, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The putative strong and weak myosin binding sites on actin are exposed and the myosin cross-bridges may cycle unimpeded. Recent work using actin mutants supports this model: charge change mutations within the trough of actin such as E311A/R312A in yeast (13) and K238A/E241A/E360H in Dictyostelium (14) result in weaker tropomyosin binding and destabilization of the on state.…”
mentioning
confidence: 79%
“…The putative strong and weak myosin binding sites on actin are exposed and the myosin cross-bridges may cycle unimpeded. Recent work using actin mutants supports this model: charge change mutations within the trough of actin such as E311A/R312A in yeast (13) and K238A/E241A/E360H in Dictyostelium (14) result in weaker tropomyosin binding and destabilization of the on state.…”
mentioning
confidence: 79%
“…Mutation to Ala could then promote reversal of strong crossbridge binding. This would explain not only the current MgATPase data (reversal before product release), but also a preliminary report using in vitro motility to examine the yeast actin mutant E311A/R312A (49). These studies showed that motility rates were similar for E311A/R312A F-actin and wild type F-actin alone, but in the presence of the regulatory proteins the sliding speed was increased for the E311A/R312A thin filaments when compared with the wild type, implying faster cross-bridge detachment.…”
Section: The Effects Of Ionic Strength On the Relative Binding Affinimentioning
confidence: 99%
“…The in vitro motility assays were performed according to previously described protocol (11,27). HMM was applied to the silicone-coated coverslips (Matsunami, Japan) at concentrations ranging from 15 to 300 g/ml.…”
Section: Preparation Of Proteinsmentioning
confidence: 99%